Falling short: examination of the validity of methods used to identify paediatric hospital falls in NSW, Australia - Daniela Feuerlicht; Maria Agaliotis; Reece Hinchcliff (Sax Institute, 2020)
Objective: Hospital falls are a major cause of costly harm. This descriptive epidemiological study reports the results of a data linkage and medical record review to examine the relative utility of these methods for identifying paediatric in-hospital falls. Type of program or service: The study was conducted across two tertiary and quaternary specialist paediatric hospitals in New South Wales (NSW), Australia. Methods: A retrospective audit was conducted of paediatric falls occurring in hospital between 1 July 2015 and 30 June 2016. Falls were identified using two systems: the Incident Information Management System (IIMS) and medical records coded data (MRCD). These data were linked, and falls were verified using medical record review. Results: Of the 146 in-hospital falls identified, only 28 (19%) were included in both systems. The IIMS identified 137 falls, with five excluded. The MRCD identified 63 admissions in which falls occurred, with 27 excluded, and screening of clinical notes found 42 falls in the remaining 36 admissions. Lessons learnt: There was a discrepancy in the number of falls identified in the two administrative datasets due to different inclusion criteria. The medical record review provided additional practice-relevant information that was unavailable within the two datasets. This descriptive epidemiological study highlights the value of combining data linkage with medical record review, but also the need for more critical reflection on the methods used to collect and report falls data in Australian hospitals, so that comprehensive and accurate data can be used to inform quality and safety interventions. This analysis will inform improvements to data capture methods and provide data to advise paediatric falls prevention strategies within the NSW paediatric hospital context.